Pengaruh Insentif, Motivasi, Lingkungan Kerja, Kepemimpinan, dan Beban Kerja terhadap Kinerja Karyawan di Bandara Adisucipto Yogyakarta - Tambunan, Nurul Afatin; Radito, Thomas Aquinas (Manajemen & Bisnis Jurnal, 2026)
This research seeks to examine the impact of incentives, motivation, work environment, leadership, and workload on employee performance at Adisutjipto Airport in Yogyakarta. It employs a quantitative approach using a survey method. Data were gathered via questionnaires distributed to 30 employees, utilizing a Likert scale. The data analysis involved multiple linear regression through SPSS software. Findings indicate that motivation significantly influences employee performance, whereas incentives, work environment, and leadership show no significant effect. Workload exerts a positive yet insignificant impact on employee performance. The coefficient of determination (R²) reveals that 79% of employee performance variations are accounted for by the variables of incentives, motivation, work environment, leadership, and workload, with the remaining 21% attributed to other factors beyond the research model. The study concludes that motivation is the most influential factor on employee performance at Adisutjipto Airport Yogyakarta.